Comparação entre métodos de administração de nutrição enteral em pacientes críticos - Araujo, Viviane Maeve Tavares de (2011)
Enteral nutrition is an integrant part in the management of critically ill patients and has a major impact on clinical outcomes of these patients. It can be administered by continuous or intermittent forms, using an infusion pump. There is a discussion, about which of these techniques shows better performance, that involves several factors such as gastric residue, respiratory infection, nausea, diarrhea, volume and calories of enteral nutrition supplied to the patient. Objectives: Compare the continuous and intermittent enteral nutrition infusion types, using as outcome volume of gastric residue, the level of caloric needs achieved daily and the clinical and metabolic alterations estimated by biochemical measurements of blood Method: Clinical, observational, prospective, randomized study, conducted in an intensive care unit, n=41 patients, divided in two groups : intermittent and continuous. The variables were: evacuations, bloating, vomiting, caloric requirements, volume of infusion and gastric residue. In all tests was set at 5% the rate of rejection of the null hypothesis Results: The measurements average of the volume of the residual gastric aspirate performed by ultrasound and manual did not differ between the groups intermittent and continuous. Most patients received more than 60% of enteral nutrition infusion during the five-days study (p = 1.0), without differences according to the supply of caloric needs. There was no statistical difference between vomiting, abdominal distention and diarrhea variables between the groups. Conclusion: The continuous or intermittent methods of enteral nutrition administration are similar when compared by the variables studied.